2018
DOI: 10.1177/2332858418802790
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Demographics, Qualifications, and Turnover of American STEM Teachers, 1988–2012

Abstract: Qualified science, technology, engineering, and mathematics (STEM) teachers are critical in the provision of high-quality STEM education for all students. Through descriptive and regression analysis, we document how demographic characteristics, qualifications, and turnover rates of a nationally representative sample of public school STEM teachers have changed from 1988 to 2012. Over this time period, STEM teachers are more likely to be female, attend selective colleges, have graduate degrees, and have STEM qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…For instance, shortages of male teachers have commonly been observed in areas such as primary education (e.g., OECD, 2018). Although the femalemale imbalance is not as much of an issue for STEM teachers (e.g., Nguyen & Redding, 2018), and although replications in other samples of prospective teachers and different educational contexts are clearly needed, our findings underline the potential usefulness of video-based SJTs including a voice-over component in decreasing gender gaps.…”
Section: Discussionmentioning
confidence: 59%
“…For instance, shortages of male teachers have commonly been observed in areas such as primary education (e.g., OECD, 2018). Although the femalemale imbalance is not as much of an issue for STEM teachers (e.g., Nguyen & Redding, 2018), and although replications in other samples of prospective teachers and different educational contexts are clearly needed, our findings underline the potential usefulness of video-based SJTs including a voice-over component in decreasing gender gaps.…”
Section: Discussionmentioning
confidence: 59%
“…For instance, shortages of male teachers have commonly been observed in areas such as primary education (e.g., OECD, 2018). Although the femalemale imbalance is not as much of an issue for STEM teachers (e.g., Nguyen & Redding, 2018), and although replications in other samples of prospective teachers and different educational contexts are clearly needed, our findings underline the potential usefulness of video-based SJTs including a voice-over component in decreasing gender gaps.…”
Section: Discussionmentioning
confidence: 60%
“…Although SJTs that measure non-cognitive attributes have generally been found to produce fewer subgroup differences than cognitive tests (e.g., Lievens et al, 2008;Whetzel & McDaniel, 2009), research indicates that members of ethnic majority groups outperform those of minority groups and females typically outperform males on SJTs (e.g., Husbands et al, 2015;Lievens et al, 2016;see Whetzel et al, 2008 for a metaanalysis). Reducing subgroup differences is critical in any selection process, but may be of particular importance for selection of prospective teachers, with a relative paucity of minority group teachers (e.g., Nguyen & Redding, 2018) representing an issue of serious and ongoing concern.…”
Section: Video-based Sjts and Subgroup Differencesmentioning
confidence: 99%
“…When we examine the teacher characteristics and school characteristics that are associated with attrition specifically to Kansas, the results indicate younger teachers and special education teachers are more at risk of turning over than their peers. Surprisingly, STEM teachers are not more likely to turn over, which recent studies using national and Kansas-specific data have also found (Nguyen & Redding, 2018;Stewart, 2018). This indicates that shortages for STEM teachers may be due to a lack of STEM teachers produced in Kansas or wanting to work in Kansas rather than that Kansas is losing too many STEM teachers.…”
Section: Discussionmentioning
confidence: 91%